Using Multidisciplinary Partnerships to Advance Juvenile Justice Reform: Experiences in 10 Communities. (May 2022) - Honeycutt, Todd; Sakala, Leah; Zweig, Janine; Hague Angus, Megan; Esthappan, Sino
The Annie E. Casey Foundation created its national deep-end initiative to support local jurisdictions to develop and implement practices, policies, and programs that prevent youth involved in the juvenile justice system—especially for youth of color—from being sent to out-of-home placements. This article presents findings about the role that partnerships played across 10 communities in the initiative, leveraging data collected through interviews and a web-based stakeholder survey. As part of the deep-end initiative, stakeholders developed partnerships with multiple entities, though they reported partnering with community organizations, youth, and families less than with juvenile justice agencies. Family engagement emerged broadly and consistently as a priority, but stakeholders infrequently mentioned youth engagement. Sites with more collaboration typically had stronger implementation, suggesting that successful collaboration goes hand in hand with implementing broader reform activities. Developing diverse partnerships to engage in juvenile justice reform is an achievable goal that can advance reform efforts.